2019
DOI: 10.1016/j.nlm.2019.107085
|View full text |Cite
|
Sign up to set email alerts
|

Working memory updating training modulates a cascade of event-related potentials depending on task load

Abstract: The brain mechanisms of working memory (WM) training in humans remain unclear. Here we examined how WM updating training modulates a cascade of event-related potentials (ERPs) elicited at different processing stages. We hypothesized that WM updating training results to decreases in the early responses reflecting stimulus selection and response preparation, and increases the late slow responses reflecting maintenance of to-be-remembered materials. Healthy adults were randomized to a WM updating group that train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
(113 reference statements)
1
13
0
Order By: Relevance
“…The N-back task requires participants to decide whether the current stimulus is as same as (match) or different from (mismatch) the one that presented n-steps previously in the stimulus sequence. Since the n-back task is frequently used in WMU-related studies ( McElree, 2001 ; Ecker et al, 2010 ; Vilà-Balló et al, 2018 ; Salmi et al, 2019 ), we used visual two-back tasks in the current study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-back task requires participants to decide whether the current stimulus is as same as (match) or different from (mismatch) the one that presented n-steps previously in the stimulus sequence. Since the n-back task is frequently used in WMU-related studies ( McElree, 2001 ; Ecker et al, 2010 ; Vilà-Balló et al, 2018 ; Salmi et al, 2019 ), we used visual two-back tasks in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Among the approved event-related potential (ERP) components triggered by each event—P1, N1, P2, N2, P3, and LPP—the P2 and P3 components were considered suitable for the current study. Modulation of the P2 component has been reported in many WMU tasks ( McEvoy et al, 1998 ; Rämä et al, 2000 ; Lenartowicz et al, 2010 ; Luu et al, 2014 ; Vilà-Balló et al, 2018 ; Salmi et al, 2019 ); it is commonly associated with primary top-down attentional control processing ( Freunberger et al, 2007 ) and useful selection of information at the sensory cortices ( Crowley and Colrain, 2004 ). Modulation of the P3 component is one of the most repeated findings in ERP studies in the field of WMU; in particular, the P3b subcomponent is related to downstream cognitive control processing and allocation of attentional resources ( Donchin et al, 1986 ; Lenartowicz et al, 2010 ; Daffner et al, 2011 ; Vilà-Balló et al, 2018 ; Salmi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these results should be interpreted with caution due to the lack of follow-ups for testing whether transfers to other cognitive domains are preserved in older individuals. Moreover, although we were aware that other ERP components might be affected by WM training, such as early visual and late positive components (LPC) (Luria et al, 2016;Salmi et al, 2019) reflecting load effect and maintenance of to-be-remembered materials (Vilà-Balló et al, 2018), it was impossible to investigate these positive and negative slow waves as they occur in a time window that overlaps our feedback stimuli and collected our button press responses. Consequently, it would have been very difficult to extract this component from the feedback stimulus and button press responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, although to a lesser extent, other ERP components might be affected as well such as the early visual ERP components-P1, N1, N2, P2 -and late positive components (LPC) or slow wave (Luria et al, 2016;Ruchkin et al, 1995). Salmi et al (2019) suggested that early and late ERPs are differentially affected by N-Back training. In particular, pre-and post-tests showed ERP changes indicative of a decreased load-effect for the training group, and slow wave amplitude that decreased in the easy task and increased in the difficult task, reflecting maintenance of to-be-remembered items (Luria et al, 2016;Vilà-Balló et al, 2018).…”
Section: Introductionmentioning
confidence: 99%